2019
DOI: 10.1111/1462-2920.14825
|View full text |Cite
|
Sign up to set email alerts
|

Lysine acetylation contributes to development, aflatoxin biosynthesis and pathogenicity in Aspergillus flavus

Abstract: Summary Aspergillus flavus is a pathogenic fungus that produces carcinogenic aflatoxins, posing a great threat to crops, animals and humans. Lysine acetylation is one of the most important reversible post‐translational modifications and plays a vital regulatory role in various cellular processes. However, current information on the extent and function of lysine acetylation and aflatoxin biosynthesis in A. flavus is limited. Here, a global acetylome analysis of A. flavus was performed by peptide pre‐fractionati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…To generate site-directed mutants, an approach of sitedirected mutagenesis was carried out according to a previously described method with minor modifications (Yang et al, 2019a). Briefly, the point-mutation fragment of the ORF, pyrG selectable marker and downstream fragment were amplified by specific primers, fused together by an overlap PCR and then transformed into protoplasts of A. flavus CA14 PTS strain.…”
Section: Mutant Strains Constructionmentioning
confidence: 99%
“…To generate site-directed mutants, an approach of sitedirected mutagenesis was carried out according to a previously described method with minor modifications (Yang et al, 2019a). Briefly, the point-mutation fragment of the ORF, pyrG selectable marker and downstream fragment were amplified by specific primers, fused together by an overlap PCR and then transformed into protoplasts of A. flavus CA14 PTS strain.…”
Section: Mutant Strains Constructionmentioning
confidence: 99%
“…To the best of our knowledge, many important PTMs (such as acetylation, succinylation, propionylation and malonylation) could provide a mechanism to respond to changes in the energy status of the cell and regulate metabolic pathways (86)(87)(88)(89)(90)(91)(92). In addition, we have previously provided the first evidence that phosphorylation, methylation, acetylation, succinylation, ubiquitination and sumoylation may be a mechanism involved in aflatoxin biosynthesis by regulating the activities of enzymes in A. flavus (72,73,85,(93)(94)(95). Therefore, the identified PTM datasets from our work may provide a foundation for studying the biological functions of these PTM events in metabolic pathways and aflatoxin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread recognition of the importance of PTMs in various biological processes (81-84), there still lack of a holistic view of PTMs events on Aspergillus proteins and the functional roles of many types of PTMs have not yet been uncovered.In this study, we identified 8,724 annotated protein-coding genes with high confidence and a significant number of these proteins were found to be modified with different types of PTMs. Although the phosphorylation, acetylation and succinylation have been reported from large-scale MS/MS studies(72,73,85), the current understanding of PTMs in Aspergillus is still limited and many important PTM events have not yet been discovered in this pathogenic fungus. Comprehensive analysis of these by guest on December 1, 2020…”
mentioning
confidence: 99%
“…AflO, a key enzyme in aflatoxin biosynthesis, was acetylated at lysine 241 and 384 and played a vital role in the pathogenicity of A. flavus ( Yang et al, 2019 ). Six proteins involved in the virulence of B. cinerea were found to be acetylated (BcSak1, Hpt1, Bcchs2, CHSV, PKS, and BOS1) ( Lv et al, 2016 ).…”
Section: Role Of Acetylation/deacetylation In Fungal Virulencementioning
confidence: 99%
“…In plant pathogenic fungi, Yang et al identified 1,313 high-confidence acetylation sites in 727 acetylated proteins in Aspergillus flavus , while 577 acetylated sites were reported in 364 different proteins in Fusarium graminearum ( Zhou S. et al, 2016 ; Yang et al, 2019 ). Several published studies have described the acetylome of different fungal species, including plant pathogenic fungi Phytophthora sojae , Botrytis cinerea , and Magnaporthe oryzae ; fungal insect pathogens, such as Beauveria bassiana and Metarhizium anisopliae ; and nonpathogenic fungi species, such as Saccharomyces cerevisiae and Yarrowia lipolytica ; which are considered as important resources to explore the physiological role of this modification in eukaryotes ( Henriksen et al, 2012 ; Mukherjee et al, 2012 ; Li et al, 2016 ; Lv et al, 2016 ; Wang et al, 2017 ; Cai et al, 2018c ; Liang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%